The Challenges of EMU Accession Faced by Catching-up Countries A Slovak Republic Case Study - Brook, Anne-Marie (OECD Economics Department Working Papers, 2005)
The Maastricht criteria for accession to the euro area can be difficult for any economy to achieve, not least because of the challenges posed by the "impossible trinity", which suggests that it is not possible to target both a stable exchange rate and stable inflation at the same time as maintaining free capital mobility. But for poorer economies which are catching up to the living standards of the wealthier EMU members, the challenges are magnified. This is because economies with very high productivity growth may have larger Balassa-Samuelson effects, resulting in higher steady state inflation rates as well as gradually appreciating equilibrium real exchange rates. While some nominal appreciation is permitted during ERM-II membership, the rules do not make it easy to signal the magnitude of expected appreciation. This may lead to poorly anchored exchange rates, making the catching-up economies more vulnerable to the challenges of the impossible trinity. Moreover, countries that have recently introduced fully-funded pension pillars which involve high transition costs, may find it difficult to meet the Maastricht criteria for government finances. It is unclear whether recent changes to the Stability and Growth Pact will alleviate the short-term fiscal pressure on countries that have improved the long-term sustainability of their government finances at the cost of short-term deterioration to their fiscal deficits. The example of Slovakia is used to illustrate these points, and a number of policy guidelines are proposed to minimise the risks. This Working Paper relates to the 2005 OECD Economic Survey of the Slovak Republic (www.oecd.org/eco/surveys/slovakia)